Changes in management policies for extremely preterm births and neonatal outcomes from 2003 to 2012: two population‐based studies in ten European regions. (5th May 2017) - Bonet, M; Cuttini, M; Piedvache, A; Boyle, EM; Jarreau, PH; Kollée, L; Maier, RF; Milligan, DWA; Van Reempts, P; Weber, T; Barros, H; Gadzinowki, J; et al.
Abstract : Objective: To investigate changes in maternity and neonatal unit policies towards extremely preterm infants (EPTIs) between 2003 and 2012, and concurrent trends in their mortality and morbidity in ten European regions. Design: Population‐based cohort studies in 2003 (MOSAIC study) and 2011/2012 (EPICE study) and questionnaires from hospitals. Setting: 70 hospitals in ten European regions. Population: Infants born at <27 weeks of gestational age (GA) in hospitals participating in both the MOSAIC and EPICE studies (1240 in 2003, 1293 in 2011/2012). Methods: We used McNemar's Chi 2 test, paired t ‐tests and conditional logistic regression for comparisons over time. Main outcomes measures: Reported policies, mortality and morbidity of EPTIs. Results: The lowest GA at which maternity units reported performing a caesarean section for acute distress of a singleton non‐malformed fetus decreased from an average of 24.7 to 24.1 weeks ( P < 0.01) when parents were in favour of active management, and 26.1 to 25.2 weeks ( P = 0.01) when parents were against. Units reported that neonatologists were called more often for spontaneous deliveries starting at 22 weeks GA in 2012 and more often made decisions about active resuscitation alone, rather than in multidisciplinary teams. In‐hospital mortality after live birth for EPTIs decreased from 50% to 42% ( P < 0.01). Units reporting more active management in 2012 than 2003 had higher mortality in 2003 (55% versus 43%; P < 0.01) and experienced larger declines (55 to 44%; P < 0.001) than units where policies stayed the same (43 to 37%; P = 0.1). Conclusions: European hospitals reporting changes in management policies experienced larger survival gains for EPTIs. Tweetable abstract: Changes in reported policies for management of extremely preterm births were related to mortality declines. Tweetable abstract: Changes in reported policies for management of extremely preterm births were related to mortality declines.